PENGARUH STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN DENGAN KEPUTUSAN KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN DALAM INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009 - Khalisa Rahmina Suryani; Redawati (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
This research aimed at empirically proving both direct and indirect influence of ownership structure to the firm value with financial decision as intervening variable on manufacturing companies listed on Indonesia Stock Exchange 2009. The object is 56 manufacturing companies listed on Indonesia Stock Exchange 2009. This research uses path analysis with SPSS 16.0 version as analizing tools. The result of this study indicate that both institutional ownership and managerial ownership directly and indirectly do not influence the investment decision, the financing decision and the dividend policy. Ownership structure does not influence the firm value.The investment decision influences the financing decision and the dividend policy but the financing decision does not influence the dividend policy. As a whole the investment decision, financing decision and the dividend policy influence the firm value